The role of the family and the school in shaping the personality of tge child an analytical study (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The present study dealt with the formation of the personality of the child within the most important institutions of social upbringing, namely: the family and the school, which was exposed to the concepts of personality, family and school, and then examined the determinants of personality structure and theories. The study dealt with the characteristics of the family and its functions and the method of social upbringing practiced in the family and how this affects the growth of the child's personality properly. So that the existing relationships within the family and meet the child's psychological and cognitive needs contribute mainly to building the child's personality and development positively. Then the research dealt with the educational institution represented by the school and the functions it should undertake to meet the basic needs of the child and thus contribute to the development of personality. Where the school integrates the individual in the community and works to develop the child's talents and capacity building and give him the opportunity to express himself and enhance his self-confidence through his participation and roles as a member of a group. The school also plays an important role in developing children's creative spirit. The study also addressed the negative effects that authoritarian methods can have on the relationship with students, which are based on violence and confiscation. The student is placed in the negative recipient location by depriving him of opportunities for expression, participation and analysis, which impairs the growth of personality and normal and healthy development. The study concluded with some suggestions and recommendations that emphasized the need for the family and the school to perform their functions in educational and psychological ways that meet the needs of children and contribute to building their personalities in a proper manner